Biologia comparada e mecanismos responsáveis pelas densidades populacionais de Mononychellus tanajoa (Bondar) e Euseius ho (De Leon) (Acari: Tetranychidae: Phytoseiidae) - Rêgo, Adriano Soares (2010)
The State of Maranhão, Brazil, is characterized by an agricultural landscape dominated by smallholder farms where slash and burn practices are used to produce staple crops such as cassava. The cultivation of cassava is key for food security and is a source of income to farmers in the Maranhão state. Cassava is attacked by several herbivores, among which the cassava green mite Mononychellus tanajoa, is considered a key pest, responsible for high losses in root yields. Predatory mites of the family Phytoseiidae are considered the most effective natural enemies for biological control of phytophagous mites in crops in greenhouses and in the field. Euseius ho is the main species of predatory mite found in cassava fields in the region of Miranda do Norte - MA. Abiotic environmental variables such as temperature, relative humidity and rainfall also influence both the populations of phytophagous mites and predatory mites in the field. We conducted laboratory and field experiments to determine the importance of the predatory mite E. ho as a biological control agent of the cassava green mite M. tanajoa as well as the relative contribution of abiotic environmental variables for the population densities of M. tanajoa and E. ho. Euseius ho had lower periods of incubation, larvae, protonymph and deutonymph as well as the period from egg to adult in comparison to those of M. tanajoa. Furthermore, the predatory mite E. ho had a high instantaneous rate of increase (ri), yet lower than that observed for cassava green mite M. tanajoa. Population densities of M. tanajoa increased over time while the population density of E. ho remained constant over the cycle of cassava. Most of the variance for the population density of M. tanajoa was explained by rainfall and relative humidity, followed by the density of E. ho and temperature. Euseius ho populations occurred in low densities throughout the year and peaked at the end of the rainy season and early dry season. The temperature was the abiotic variable that explained most of the variance for the population density of E. ho, followed by the density of M. tanajoa, rainfall and relative humidity in cassava. In conclusion, the predator mite E. ho contributed to the regulation of cassava green mite M. tanajoa, but the main mechanisms explaining the population densities of M. tanajoa and E. ho were environmentalabiotic variables